2017
DOI: 10.1021/acs.biochem.7b00635
|View full text |Cite
|
Sign up to set email alerts
|

Activation Mechanism of the Streptomyces Tyrosinase Assisted by the Caddie Protein

Abstract: Tyrosinase (EC 1.14.18.1), which possesses two copper ions at the active center, catalyzes a rate-limiting reaction of melanogenesis, that is, the conversion of a phenol to the corresponding ortho-quinone. The enzyme from the genus Streptomyces is generated as a complex with a "caddie" protein that assists the transport of two copper ions into the active center. In this complex, the Tyr residue in the caddie protein was found to be accommodated in the pocket of the active center of tyrosinase, probably in a ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 58 publications
1
21
0
4
Order By: Relevance
“…The newly added oxygen (Oζ2) is within the coordination bond distance from Cu A-3 and near to Cu B-2 (S1E Fig). The complex between Cu A-3 and the oxygenated Tyr 98 may correspond with the Cu(II)-bound dopasemiquinone observed in the solution state [29]. Specifically, Cu A-3 is in a bipyramidal trigonal coordination cage, in which the axial ligands are the Oζ2 atom added to the caddie Tyr 98 and the Nε atom of His 38 , and equatorial ligands are the Oη atom of the caddie Tyr 98 , the Nε atom of His 54 , and the bridging oxygen atom at the Wat 3 site.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The newly added oxygen (Oζ2) is within the coordination bond distance from Cu A-3 and near to Cu B-2 (S1E Fig). The complex between Cu A-3 and the oxygenated Tyr 98 may correspond with the Cu(II)-bound dopasemiquinone observed in the solution state [29]. Specifically, Cu A-3 is in a bipyramidal trigonal coordination cage, in which the axial ligands are the Oζ2 atom added to the caddie Tyr 98 and the Nε atom of His 38 , and equatorial ligands are the Oη atom of the caddie Tyr 98 , the Nε atom of His 54 , and the bridging oxygen atom at the Wat 3 site.…”
Section: Resultsmentioning
confidence: 99%
“…In the previous study [29], we demonstrated that the addition of NH 2 OH stimulates the caddie proteins to aggregate, resulting in the release of tyrosinase from the complex. The aggregation is likely triggered by the formation of reactive dopaquinone on the caddie Tyr 98 residue.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations